An Analysis of Satire as Social Critique in Jonathan Swift’s A Modest Proposal - Wafiq Aziz Wardah; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the use of satire as a form of social critique in Jonathan Swift’s A Modest Proposal (1729), a canonical satirical essay that responds to the severe poverty and political oppression in 18th-century Ireland. The research adopts a descriptive qualitative method with M.H. Abrams’ theory of satire as the analytical framework, focusing on four key elements: parody, irony, allegory, and humor. Through close reading and contextual analysis, the study reveals how Swift weaponizes rhetorical strategies to expose the moral failures of British colonial rule, the economic exploitation of the Irish poor, and the inhumanity of utilitarian logic. Findings show that Swift employs layered irony and grotesque parody to mimic policy discourse, turning bureaucratic language into a tool of condemnation. Allegorical expressions and dark humor further intensify the satirical impact, forcing readers to confront the ethical absurdity of commodifying human lives. The study concludes that Swift’s satire is not merely literary art, but a powerful moral act of resistance that remains relevant to contemporary critiques of injustice, inequality, and systemic indifference.